Molecular variants of Leishmania (Viannia) braziliensis trigger distinct patterns of cytokines and chemokines expression in golden hamster. (February 2019) - Rêgo, Felipe Dutra; Fradico, Jordana Rodrigues Barbosa; Teixeira-Carvalho, Andréa; Gontijo, Célia Maria Ferreira
Highlights: Immune response of golden hamsters infected with genetic-variants of L. braziliensis . Distinct gene expression profiles of cytokines/chemokines due L. braziliensis strains. L. braziliensis strains-segregations due to the identification of potential biomarkers during the disease progression. Abstract: Cutaneous leishmaniasis (CL) mainly caused by Leishmania braziliensis is a chronic inflammatory disease widely spread in Brazil. Genetic variant strains of this parasite have been associated with atypical clinical manifestations of CL in an endemic area in Brazil. Furthermore, these strains have presented distinct biological behaviors in golden hamster, suggesting differential activation of the immune response. In the present study we proposed to evaluate the localized immune response in golden hamsters infected with known molecular variant strains of L. braziliensis, in distinct time points post-infection (PI). Detailed analyses of the mRNA expression of cytokines and chemokines in hamster-skin lesions were performed. Heat map matrix and hierarchical cluster analysis were carried out to segregate the strains due to mRNA expression. Distinct patterns of immune response were found in both time points, more evident in the recent-phase disease (30 days-PI). At this time point, the genetic variant strains expressed high levels of tnfα, il12 and tgfβ whilst the non-variant strain expressed ifnγ, il6, il4, il10, il13 and ccl17 . The hierarchical clustering highlights this distinct pattern in which all genetic variant strain was grouped in the cluster I and the non-variant strain grouped into the cluster II. At late-phase disease (60 days-PI) all isolates expressed high levels of il4 and il10 . The non-variant strain shown a significant reduced expression of ifnγ, il6, ccl17, and ccl22 whilst distinct patterns were observed for the genetic variant strains. For the first time, a large panel of cytokines and chemokines mRNA-expression was analyzed in experimental trials using golden hamsters as animal model and genetic variant strains of L. braziliensis . Our findings suggest that genetic variant strains of L. braziliensis are able to trigger differential gene expression of cytokines and chemokines in the skin lesion from infected hamsters. The parasite intrinsic ability to activate distinct pathways in the host-parasite interaction may be associated to the large spectrum of clinical manifestation observed in CL-patients.